The role of alpha defensin in prosthetic joint infection (PJI) diagnosis: a literature review. Issue 1 (January 2019) - Bonanzinga, Tommaso; Ferrari, Matteo Carlo; Tanzi, Piergiuseppe; Vandenbulcke, Filippo; Zahar, Akos; Marcacci, Maurilio
Abstract : Prosthetic joint infection (PJI) management is not standardized worldwide and the outcome is frequently unsatisfactory. More and more arthroplasties are now being performed. An increasing number of highly virulent and antibiotic-resistant bacteria and an ageing population of patients presenting with many comorbidities make it necessary to focus on this important topic. Diagnosis of PJI remains challenging because the clinical signs and symptoms and elevation of systemic biomarkers (C-reactive protein, erythrocyte sedimentation rate) may be unclear. In the last few years, the clinical research has focused on synovial fluid biomarkers as a possible breakthrough in the complex scenario of PJI diagnosis. Synovial biomarkers have shown encouraging results and they should be used as diagnostic adjuncts to synovial white cell count and culture bacteriology. Synovial leukocyte esterase (LE) and synovial C-reactive protein (CRP) have been evaluated as good screening measures; however, the most promising synovial fluid biomarker in terms of sensitivity and specificity for PJI seems to be alpha defensin (AD). The laboratory-based alpha defensin enzyme-linked immunosorbent assay (ELISA) test demonstrated the highest ever reported accuracy for PJI diagnosis. However, an alpha defensin lateral flow test could have its place in ruling in a suspected PJI intraoperatively because of its high specificity and rapid results. Cite this article: EFORT Open Rev 2019;4:10-13. DOI: 10.1302/2058-5241.4.180029